Evolutionary Pattern of Asian HIV-1 Subtype B from 1990 to 2007: In Silico Analysis Based on Envelop Protein - Sobia Kanwal; Tariq Mahmood (The Scientific World Journal)
HIV-1 envelop gene is a major target for vaccine development. Envelop protein and its V3 loop is shown to be important determinant of HIV-1 pathogenecity. Herein, the evolutionary pattern of most prevalent HIV-1 subtype B in Asia is determined by analyzing envelop protein and V3 domain based on the 40 randomly selected sequences of HIV-1 from database (Los Alamos), divided into four groups since 1990–2007. Construction of envelop protein phylogeny by using MEGA 5 exhibit the active mutation pattern, increase in potential N-glycosylation sites which were predicted by using online software SignalP-NN. An online available tool Drawgram was used for multiple sequence alignment (MSA) of HIV-1 subtype B envelop region and V3 loop while the alignment was rechecked by using CLUSTAL W and further was analyzed for GPGX motif and conserved region in V3 loop. Variation at fourth position of the GPGX motif and 60% conservation was found in V3 loop. Hence, this diversifying pattern of envelop protein in the Asia formulates the HIV-1 strains more pathogenic during the period of 17 years. These findings might help in understanding significant structural and functional constrains of the mutant viral strains and ultimately in vaccine development.